FENOMENA KOMUNIKASI ANAK JALANAN DI PASAR 45 KOTA MANADO - Hamonangan, Adventus Daniel (ACTA DIURNA KOMUNIKASI, 2013)
This research is entitled Street Children Communication Phenomenon at Pasar 45 Manado, with the purpose of this is to know the phenomenon and the obstacles of their communication as Pasar 45 Manado. The theory used is Alfred Schutz Phenomenology Theory which is mainly prioritizing the subjectivity of using street children as the informers, and using qualitative methods approach to street children phenomenon. The result of this research are some factor in their life that can strengthen their perception that living as street children can fulfill their needs, their relationship and even can help them to solve the problem they have as street children. This perception finally makes them communicate very often both verbally and non-verbally with their society, street children and non street children. The obstacles of problems they have are the differences of Field of Experiences and Frame of References among street children and people in their surrounding. 4 factors that researcher found are economical factor, family disharmony, street life and outside perceptions.